Prediction of splitting crack growth in prestressed concrete members using fracture toughness and concrete mix design. (20th June 2020) - Shafiei Dastgerdi, Aref; Peterman, Robert J.; Savic, Adrijana; Riding, Kyle; Beck, B. Terry
Highlights: Splitting-crack growth propensity was predicted by fracture toughness and mix design. Angularity and volume of coarse aggregates significantly affect splitting crack growth. Fracture toughness and splitting crack length are highly correlated at low strength. For a given wire type and edge-distance, there is an optimum mix design. Abstract: In this study, the effect of concrete mix design on end-splitting cracks in prestressed concrete members was examined. The concrete material needs to be resistant to splitting-crack growth at the strengths at which the pretensioned member is detensioned. Mixtures with variable coarse aggregate volume, angularity, and water-to-cementitious ratio were designed and Fracture toughness tests on 4 three-point bending concrete specimens for each mix were carried out. Next, pretensioned prisms with three different reinforcement edge distances 0.750, 0.625 and 0.500 in. (19 mm, 16 mm and 13 mm) were fabricated and detensioned when the concrete compressive strength reached 4500 psi (31 MPa). Splitting cracks were quantitatively evaluated by direct measurement. The results indicated a strong correlation between crack length measurements and fracture toughness. Additionally, a linear regression model was developed by which splitting-crack growth in prestressed cross-sections with varied edge-distance thickness can be predicted. The findings from this study could lead to a significant improvement in splitting crack resistance in pretensioned concrete members where the high amount of transverse stress is often introduced at low compressive strengths.